2020
DOI: 10.1167/tvst.9.7.19
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting MAIA Microperimetry Using Age- and Retinal Loci-Specific Reference Thresholds

Abstract: Macular Integrity Assessment (MAIA) microperimetry is used widely in clinical trials and routine practice to assess paracentral scotoma. Current interpretation of MAIA is based on an assumed uniform 25 decibel (dB) cutoff for normal function irrespective of subject age and retinal location. We examined this convention by establishing an ageand loci-specific reference in healthy eyes and comparing this to the <25 dB cutoff. Methods: Retrospective MAIA results from healthy eyes were analyzed for prevalence of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Bland-Altman analyses showed that for the BE and the WE the bias was −0.13 log deg 2 (95%CI from −0.41 to 0.12), and 0.0 log deg 2 (95%CI from −0.28 to 0.27), respectively. The 95% limits of agreement were large: ±1.09 log deg 2 for the BE and ±1.01 log deg 2 for the WE. A significant correlation between the average and the difference of the first fixations recorded with the two instruments was detected for the BE (r(18) = 0.59, p = 0.007) and for the WE (r(15) = 0.56, p = 0.02), indicating that a proportional bias exists.…”
Section: Inter-device Repeatability Of 20 S Fixation Stabilitymentioning
confidence: 85%
See 1 more Smart Citation
“…Bland-Altman analyses showed that for the BE and the WE the bias was −0.13 log deg 2 (95%CI from −0.41 to 0.12), and 0.0 log deg 2 (95%CI from −0.28 to 0.27), respectively. The 95% limits of agreement were large: ±1.09 log deg 2 for the BE and ±1.01 log deg 2 for the WE. A significant correlation between the average and the difference of the first fixations recorded with the two instruments was detected for the BE (r(18) = 0.59, p = 0.007) and for the WE (r(15) = 0.56, p = 0.02), indicating that a proportional bias exists.…”
Section: Inter-device Repeatability Of 20 S Fixation Stabilitymentioning
confidence: 85%
“…The repeatability did not improve: for the BE, the bias was −0.14 log deg 2 and the 95% limits of agreement were ±1.12 log deg 2 . For the WE, the bias was −0.004 log deg 2 and the 95% limits of agreement were ±1.06 log deg 2 . In addition, the proportional bias persisted: the correlation…”
Section: Bivariate Contour Ellipse Area (Bcea) Calculated From the Ey...mentioning
confidence: 93%
“…Quantile regression was utilised to establish loci-and age-specific reference from healthy eyes as previously reported [8]. In brief, at each locus, retinal sensitivity was plotted against age, and quantile regression was utilised to establish the 95% prediction interval [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the study recruited patients with intermediate AMD, hence the impact of coexisting soft drusen and hyper-pigmentation may have confounded the results. Furthermore, the comparison was not controlled for age and spatial distribution given the normative values for microperimetry sensitivity changes with age [8,9] and retinal eccentricity [8,10] in healthy eyes. Therefore, small but significant functional changes may be masked by analysis of mean sensitivities alone.…”
Section: Introductionmentioning
confidence: 99%
“…There are known age-related changes in perimetry. However, investigations into age-related normative values in microperimetry are limited 12 , 13 and therefore are not yet a part of the standard MAIA output. Historically, volumetric data have not been commonly used due to the difficulties in coding custom programs for the task of three-dimensional rendering.…”
Section: Introductionmentioning
confidence: 99%